DEVELOPMENT OF HUMAN RIGHTS COURT FROM TIME TO TIME IN LAW ENFORCEMENT IN INDONESIA - Suryaningrat, Seno Aji (Faculty of Law, Khairun University, 2022)
Court of Human Rights is a special court below the General Court that located in the Regency/City which jurisdiction includes in its District Court. The authority of the Court of Human Rights is tasked to examine and rule on cases of human rights violations, investigate and adjudicate serious violations of human rights which heavily committed outside the territorial boundaries of the Republic of Indonesia by an Indonesian citizen. Court of Human Rights, which adjudicate cases of gross human rights violations in East Timor Polls Post-defendants have been executed by both military and civilian, and was decided by the Court of Human Rights under law No. 26 Year 2000 regarding Human Rights Court